Implementasi E-Court dalam Proses Beracara di Pengadilan - Jane Shirley Wambrauw (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2022)
This study aims to examine how e-Court is applied in a judicial environment based on Supreme Court Regulation (Perma) No. 1 of 2019. This research applies an empirical juridical approach. The results showed that the implementation of e-Court specifically at Biak’s District Court was applied only to the e-Payment process. Apart from that, Biak’s District Court has not maximally implemented this e-Court application, due to the letter of the Secretary of the Supreme Court No. 630/SEK/SK/VII/2019 which explains that the court appointed as a pilot in implementing e-Court in the judicial environment. In addition, to support the good implementation of e-Court, human resources who understand digital literacy are needed to realize fast and low-cost justice.